Performance and Emissions Characteristics of Vehicle Fuelled with Blended Palm Biodiesel Before and After Engine Overhaul - Zulkifli, Abd Fathul Hakim; Mohd Ali, Mas Fawzi; Anwar Syahmi Adlin Zafrulan, Anwar Syahmi Adlin Zafrulan; Osman, Shahrul Azmir; Abd Jalal, MZahar; Harrison Lau, Harrison Lau (semarak ilmu, 2024)
Rapid industrialization and growth in population have resulted in a rapid increase in energy demand. Pollutant emissions from diesel engines have caused major impacts in disturbing the ecological system. The Malaysian government implemented the B10 biodiesel program for the transportation sector and B7 for the industrial sector in 2019 to drive the demand for palm oil and increase the sustainability of energy resources. For future implementation, the government is looking toward for higher percentage of blended biodiesel, such as B30 and above. This paper presented the effect of engine overhaul on the performance and emissions of a vehicle fuelled with blended biodiesel (B10, B20 & B30) by comparing before and after the engine overhaul. By using a vehicle Toyota Hilux 2.5L, the vehicle was attached to a chassis dynamometer for determining its performance such as brake power and brake specific fuel consumption (BSFC) at 45% and 90% of Acceleration Pedal Position (APP), respectively. The exhaust gas emissions were measured using a 5-channel analyser for determining the carbon dioxide (CO2), carbon monoxide (CO) and nitrogen oxide (NOx). The experiment was conducted in a steady-state condition with a constant speed of 30, 60, 90, and 110 km/h simulating rural, urban, and motorway speeds. The performance results revealed that blended biodiesel B10, B20 and B30, produced higher brake power, and lower brake-specific fuel consumption after engine overhaul. Emissions results showed that CO was increased at 45% APP but decreased at a higher 90% APP, and in most cases, NOx and CO2 emissions were decreased with an increase in speed for both APP.